Theoretical Analysis and Optimization Strategies of Wavefront Errors and Chromatic Aberrations Induced by Optical Coatings - Yang Gao; Liang Miao; Xin-Dong Chen; Xin Zhang; Cheng-Gang Mo (Photonics)
This research addresses the frequently overlooked wavefront errors and chromatic aberrations in optical coatings. It identifies intrinsic phase shifts within the coating system as the primary cause of these aberrations, rather than errors in surface form accuracy. This study investigates the impact of group delay (<semantics>GD</semantics>) on wavefront errors in optical coatings. The results reveal that <semantics>GD</semantics> contributes significantly to wavefront errors in two cases: when coatings exhibit thickness non-uniformity and when they operate over a wide range of incident angles. At a single incident angle, wavefront errors are only induced when both <semantics>GD</semantics> and thickness non-uniformity exist. In the case of a wide range of incident angles, even in the absence of thickness non-uniformity, <semantics>GD</semantics> still introduces wavefront errors. This study introduces novel optimization strategies for thin-film components through theoretical derivation, aiming to minimize wavefront errors by optimizing <semantics>GD</semantics>.